Effects of Metformin, Avocado Seed, and Diabetic Ingredients Infusion to Weight and Fasting Blood Glucose on Sucrose Diet Rats - Jasaputra, Diana Krisanti; Wargasetia, Teresa Liliana; Elizabeth, Elizabeth (Universitas Islam Bandung, 2019)
Metformin, an oral hypoglycemic drug which has metabolic effects and weight loss after 6–9 months; however, after 18 months, these effects disappear. Oral hypoglycemic drugs with no effect on raising the weight are needed. The objective of the study is comparing the effects of metformin, avocado seed infusion (AS), and diabetic ingredients/DI (green chiretta, Java tea, and bitter grapes) in increasing weight and fasting blood glucose of rats with sucrose diet. The research was conduct at the Pharmacology Laboratory, Faculty of Medicine Universitas Kristen Maranatha in February–August 2017. The results showed that metformin within six weeks reduced weight (75.55%) compared to control (+) with a hypercaloric diet (114.36%). Metformin and hypercaloric diet in rats for 14 weeks showed a 125.66% increase in weight, higher than control (+) (114.36%), although not significant (p>0.05). Weight in rats with hypercaloric and AS diet for 14 weeks was 94.30% and 81.68% in DI was lower than control (+) (114.36%), but not significant (p>0.05). Fasting blood glucose (FBG) of dietary hypercaloric rats and metformin was 123.75 mg/dL, higher than control (+), which was 85.75 mg/dL (p<0.01), whereas FBG infusion of AS and DI during 14 weeks: 85.75 mg/dL, and 99.50 mg/dL, not significant to control (+) (p>0.05). In conclusions, metformin increased rats body weight even though not significantly and fasting blood glucose in rats fed a hypercaloric diet for 14 weeks, while avocado seed infusion and diabetec ingredients infusion did not. EFEK METFORMIN, INFUSI BIJI ALPUKAT, DAN INFUSI RAMUAN DIABETES TERHADAP BERAT BADAN DAN GLUKOSA DARAH PUASA PADA TIKUS DIET SUKROSAMetformin, obat hipoglikemik oral berefek metabolik dan menurunkan berat badan (BB) setelah 6–9 bulan, namun setelah 18 bulan efek ini hilang. Diperlukan obat hipoglikemik oral yang tidak berefek meningkatkan BB. Tujuan penelitian ini membandingkan efek metformin, infusi biji alpukat (BA), dan infusi ramuan diabetes/RD (sambiloto, kumis kucing, dan bratawali) dalam meningkatkan BB dan glukosa darah puasa pada tikus diet sukrosa. Penelitian dilaksanakan di Laboratorium Farmakologi, Fakultas Kedokteran Universitas Kristen Maranatha periode Februari–Agustus 2017. Hasil penelitian menunjukkan metformin dalam waktu 6 minggu mengurangi penambahan BB (75,55%) dibanding dengan kontrol (+) diet hiperkalori (114,36%). Pemberian metformin dan diet hiperkalori pada tikus selama 14 minggu menunjukkan kenaikan BB 125,66%, lebih tinggi dibanding dengan kontrol (+) (114,36%), walaupun tidak signifikan (p>0,05). Berat badan pada tikus dengan diet hiperkalori dan infusi BA selama 14 minggu adalah 94,30% dan RD 81,68%, lebih rendah dibanding dengan kontrol (+) (114,36%), namun tidak signifikan (p>0,05). Glukosa darah puasa (GDP) tikus diet hiperkalori dan metformin adalah 123,75 mg/dL, lebih tinggi dibanding dengan kontrol (+) 85,75 mg/dL (p<0,01), sedangkan GDP infusi BA dan RD selama 14 minggu adalah 85,75 mg/dL dan 99,50 mg/dL, tidak signifikan terhadap GDP kontrol (+) (p>0,05). Simpulan, metformin meningkatkan berat badan tikus walau tidak signifikan dan meningkatkan glukosa darah puasa pada tikus diet hiperkalori selama 14 minggu, sedangkan infusi biji alpukat dan ramuan diabetes tidak.